Enterprising Africa transformation through entrepreneurship - Dobson, Stephen; Agyapong, Daniel; Jones, Paul; Maas, G. (Gideon), 1959- (London : Routledge, 2020)
Enterprising Africa explores the future opportunities, challenges, growth areas and key themes that will shape entrepreneurship in the African continent over the next decade. Entrepreneurship can be the key to unlock resilient growth, but only if it is driven byboth socially productive and growth-oriented new businesses. The book considers entrepreneurship as an enabler for socio-economic growth and development in Africa, especially in the context of youth unemployment and increasing youth population for which the traditional, and indeed emerging, industrial sectors will not be able to produce sufficient jobs to meet demand. Organised around three thematic parts, Part I covers the notion of inclusive growth and the role that entrepreneurs can play supporting this. Part II considers the dynamic between entrepreneurs and the environment since social, economic and environmental concerns need to build upon each other rather than vie for recognition. Finally, Part III offers chapters exploring policy contexts and the wider institutional ecosystems that need to be developed and enhanced to ensure a strong and vibrant environment for the future entrepreneurs of Africa to thrive. Edited and authored by leading experts in the field, this fascinating text will be of interest toacademics as well as students of International, Transformational and Social Entrepreneurship, andInternational and African Business.
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship -- Africa; Economic development -- Africa; Social responsibility of business -- Africa; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Entrepreneurship